Corrigendum to "Effects of Cannabinoid Exposure during Adolescence on the Conditioned Rewarding Effects of WIN 55212-2 and Cocaine in Mice Influence of the Novelty-Seeking Trait" - Rodríguez-Arias, M (Neural plasticity, 2016)
[This corrects the article DOI: 10.1155/2016/6481862.]